A survey on information extraction technology based on remote sensing big data - Weiquan LIU; Cheng WANG; Yu ZANG; Qian HU; Shangshu YU; Baiqi LAI (大数据)
With the rapid development of remote sensing technology, our country has established a relatively complete space remote sensing and flexible and diverse aerial remote sensing data acquisition system.Remote sensing big data is mainly based on massive remote sensing data, integrating other multi-source remote sensing data, using big data thinking and methods, and discovering knowledge laws and high-value information in massive data.Firstly, the research work of information extraction technology based on remote sensing big data was reviewed in recent years.Secondly, the development history of remote sensing information extraction technology was expounded from three aspects: remote sensing target detection, remote sensing surface object segmentation, and remote sensing change detection.Finally, the information extraction technology based on remote sensing big data was sorted out, summarized and prospected.